Dynamics Analysis and Optimization of Automotive Transmission - Zhang Jiping; Meng Fanlong; Ma Weijin; Wang Zhijian (Jixie chuandong)
According to the problem that a certain type of automotive transmission case in the sale is easy to crack,the finite element modal analysis and operational modal tests of automotive transmission are carried out and the modal parameters of transmission are obtained. Then,the reliability of the results is verified by the modal correlation matrix. On this basis,through comparing the results between simulation and experiment,the correctness and reliability of the simulation analysis are proved. The mode shapes which prone to fatigue cracking are analyzed. Finally,from the perspective of the frequency shift,the installation type of the powertrain is optimized,the overall stiffness of the transmission is improved,the test results provide method and theoretical basis for avoiding the transmission case cracking.